ETUC annual gender equality survey 2017 - 10th edition - - Fulton, Lionel; Sechi, Cinzia; Helfferich, Barbara (Brussels, 2017)
"As part of the follow-up to the ETUC Congress engagements towards the promotion of women within its membership and decision-making structures, in 2017 the ETUC carried out the tenth edition of its Annual Gender Equality Survey (previously known as the 8th March survey). The aim of this survey is to monitor the proportion of women in the European trade union movement, including in decision-making positions and bodies. The objective is to assess progress in reducing the representation and decision-making gap between women and men in trade unions.